EXAMINATION OF POSSIBLE LINKS BETWEEN DRUG RESISTANCE AND MORPHOLOGY OF LUNG IMAGES OF TUBERCULOSIS PATIENTS - V. A. Kovalev; V. A. Liauchuk; I. U. Safonau; A. U. Tarasau (Informatika, 2016)
The purpose of this paper is to present the results of an exploratory study of possible correlations between the drug resistance and the structural features of CT and X-ray images of lungtuberculosis patients. A multi-step procedure is suggested which includes calculation of textural image features, extracting their principal components, correlating them to patients’ clinical data and mapping the significant principal components back to image descriptor elements and then to the corresponding image structures they found to be linked with. The results of a detailed statistical analysis of the revealed links between the drug resistance and the image features are presented. The analysis includes findingone-factor correlations, performing multivariate regression analysis and cross-validation.